PROBLEMS IN THE FIELD OF TRANSLATION (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This paper examines the major problems translators encounter in their work, including semantic ambiguity, cultural gaps, idiomatic expressions, and stylistic variations. By analyzing these challenges through practical examples and theoretical frameworks, we aim to provide insights into the complexities of translation and suggest approaches for overcoming these obstacles. The study emphasizes that translation is far more than literal word replacement—it is a nuanced process of meaning reconstruction across linguistic and cultural boundaries.